PLASTIC RECYCLE IN CIRCULAR ECONOMY : ECONOMIC & ENVIRONMENTAL IMPROVEMENTS - Setiyo Purwanto; Nur Endah Retno Wuryandari; Rizka Amalia Nur Hasana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Environmental issues have become a global concern regarding the increasing impact of damage by company operations such as greenhouse gas emissions and toxic toxins, piles of plastic waste etc. This research aims to test the implementation of the circular economy concept which is influenced by the effects of the supply chain, green environment and economic growth through the recycled plastic industry. This research is based on a quantitative methodology with population data coming from members of ADUPI within the scope of plastic recycling industry activities in the DKI Jakarta area and its surroundings. The respondent sample data collection technique used the purposive random sampling method which was calculated using the SmartPLS statistical application program. The findings of this research indicate that the application of the circular economy concept in the research area has had little impact on environmental change for the better, reducing the burden of environmental pollution only. Apart from that, the length of the plastic recycling process for the output process is not commensurate with the significant economic added value to increase the community's economic growth. However, the overall effect of supply chain activities has a positive contribution to the implementation of the circular economy concept of 50.5%.